Nitrogen topdressing at different phenological stages on common bean changes grain yield and quality - Nogueira, Gabriel Pereira [UNESP]; Goncalves Silva, Mateus Sebastiao [UNESP]; Leal, Fabio Tiraboschi [UNESP]; Farinelli, Rogerio [UNESP]; Checchio Mingotte, Fabio Luiz [UNESP]; Lemos, Leandro Borges [UNESP] (Univ Federal Mato Grosso, 2019)
The need to know the nitrogen uptake (N) by common bean is important to understand the productive and qualitative performance of this crop. The objective of this study was to evaluate the influence of nitrogen topdressing as a function of different phenological stages on the morphometric and productive performance, and on the technological characteristics of the bean grains grown under conventional soil preparation. A randomized block design with four replications was used. The treatments were constituted by twelve topdressing N supply combinations (NS) (total dose = 90 kg ha(-1) N) applied in the phenological stages V-3, V-4 and R-5 (V-3+ V-4+R-5) of irrigated winter bean: 00+00+00; 30+30 +30; 30+60+00; 30+00+60; 60 + 30 + 00; 00+60+ 30; 45+45+00; 00+45+45; 45+00+ 45; 90+00+00; 00+ 90+00; and 00+00+90. The source of N used was conventional urea. NS 30 + 00 + 60, 00 + 45 + 45 and 45 + 00 + 45 increase grain yield and agronomic efficiency in relation to the absence of N and single dose application at V-4 phenological stage of common bean. The highest crude protein yields and the shortest cooking time were provided by FN 00+45+45, 45+00+45, 90+00+00, 00+90+ 00 and 00+00+90.
Keywords: Phaseolus vulgaris; N splitting; agronomic efficiency; grains technology